Investigating interplay between mitochondrial dna mutations, oxidative stress and cell deaths in Malaysian breast cancer patients - Omasanggar, Raevathi (2021)
Mitochondrial DNA (mtDNA) mutations, oxidative stress and resistance to cell deaths increase one’s risk for breast cancer. This study aims to identify the types of mtDNA mutations, levels of protein expression of oxidative stress, apoptosis, autophagy and mitophagy in breast cancer as well as the association between mtDNA mutations and the levels of protein expression. Female breast cancer patients (n=20) without neoadjuvant treatment were recruited with informed consents. Samples were 20 matched breast tumours with corresponding normal breast tissues. The entire mtDNA (16.6 kb) was sequenced using next-generation sequencing (NGS) and the levels of protein expressions were studied using tissue microarray and immunohistochemistry. A total of 18 of 20 patients had at least one somatic mtDNA mutation in their tumour samples. Overall, 65 somatic mutations were identified, with 30 novel mutations. The majority (59%) of the somatic mutations were in the coding region, whereas only (11%) of the mutations occurred in the D-loop. Notably, (15.4%) of somatic mutations in the protein-coding regions were potentially deleterious. A total of 753 germline mutations were identified and four of which were novel mutations. In comparison to somatic mutations, <1% of germline mutations are harmful. Immunohistochemistry study showed inconsistent expressions of MnSOD2, LC3B, BNIP3 and Parkin in breast cancer tissues. The expression of Beclin-1 was consistently positive and the expression of CC3 was consistently negative in all breast cancer cases. The differences in Beclin-1 expression between cancer and matched normal tissues were significant (p<0.001). Investigation of the relationship between somatic mtDNA mutations and protein expression levels of MnSOD2, CC3, LC3B, Beclin-1, BNIP3 and Parkin showed no significant differences. The findings of this study may enhance the current knowledge of mitochondrial-regulated cell mechanisms in breast cancer in Malaysia.